2021
DOI: 10.1111/odi.13931
|View full text |Cite
|
Sign up to set email alerts
|

Novel recurrence risk stratification of odontogenic keratocysts: A systematic review

Abstract: The aim of this study was to identify all clinical, radiological, histopathological, and immunohistochemical features associated with recurrence of odontogenic keratocysts (OKCs) in the literature and formulate a recurrence risk stratification based on these findings. A search was performed in PubMed/Medline, Scopus, Web of Science, Google Scholar and Cochrane databases for clinical and laboratory studies reporting on clinico‐pathological features that led to OKC recurrences for the period 2000 to 2020. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Parameters like gender distribution and age distribution was in the similar manner as reported in previously studies. 12,13 In our study males were predominant victims and usually were in their forties. Paradoxical to age distribution among enrolled participants in one study age ranged from 5 to 86 years 14 .…”
Section: Discussionmentioning
confidence: 51%
“…Parameters like gender distribution and age distribution was in the similar manner as reported in previously studies. 12,13 In our study males were predominant victims and usually were in their forties. Paradoxical to age distribution among enrolled participants in one study age ranged from 5 to 86 years 14 .…”
Section: Discussionmentioning
confidence: 51%
“…Aggressive methods include peripheral osteotomy, cryotherapy (with liquid nitrogen) and application of Carnoy’s solution 18 , 19 . Marsupialization and decompression have been shown to be effective in the management of extensive OKCs with a lower recurrence rate when compared to enucleation alone 20 , 21 . Chemical cautery with the application of Carnoy’s solution has been shown to reduce the recurrence rate; however, it has been banned in some countries due to its suspected carcinogenic effects 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the mentioned index is capable of predicting recurrence in oral SCC lesions. Also Titinchi ( 2022 ), in a systematic review article, formulated a recurrence risk stratification by Ki67 and AgNOR and other parameters such as age and size of the lesion. By investigating several studies, they stated that there is a strong relationship between expression of Ki67 and AgNOR and tendency of OKC for recurrence.…”
Section: Discussionmentioning
confidence: 99%